Characterization, comparative analyses, and phylogenetic implications of mitochondrial genomes among bark and ambrosia beetles (Coleoptera: Curculionidae, Scolytinae) - Guo, Qiuhong; Huang, Weidong; Sang, Wen; Chen, Xiaosheng; Wang, Xingmin (Frontiers in Ecology and Evolution, 2023)
Bark and ambrosia beetles of Scolytinae are well-known forest pests which can cause significant economic losses to trees and timber. Comparative analyses of structural characteristics of mitochondrial genomes (mitogenomes) and phylogenetic analyses could significantly improve our understanding of mitogenomic evolution and evolutionary history of this important group. Here, we have assembled new mitogenome data of four taxa (Euwallacea interjectus, E. fornicatus, E. similis, and Xylosandrus sp.) and presented a comparative analysis with available mitogenomes of Scolytinae. Phylogenetic analyses of Scolytinae were also conducted with different methods and datasets. The four mitogenomes are 15,419 to 16,265 bp in length and contain 13 protein-coding genes (PCGs), 22 transfer RNA genes, two ribosomal RNA genes and a control region, except for E. similis wherein the trnI is not detected. All PCGs initiate with either standard start codon of ATN or nonstandard GTG/TTG. TAA codon is used for termination more than TAG and incomplete T. The analysis of nonsynonymous/synonymous mutation ratio (Ka/Ks) of PCGs suggests the highest and lowest evolutionary rates are within nad4 and cox1, respectively. The heterogeneity analyses of different mitogenomic datasets show excluding the third-codon positions from the datasets largely reduce their heterogeneity. Our phylogenetic analyses derived from mitogenome data provide new evidence toward the revision of the distinguishing characteristics of related genera in this subfamily and highly supported most of nodes at deeper and shallow level. The present study highlights the utility of mitogenome data for resolving the phylogenetic framework of bark and ambrosia beetles, although more taxa sampling is needed to elucidate the complicated relationships of Scolytinae.